Improving Rural Women income through Cocoyam Value Addition Technologies in Abia State, Nigeria - Lovina Odoemelam; Gideon Onuekwusi; Rose Kanu (Journal of Agricultural Extension, 2017)
The National Root Crops Research Institution (NRCRI) Umudike embarked on massive capacity building and extension of technologies of new and improved food forms of cocoyam to rural farmers/women groups from 2005 to date in this country generally and south-east agricultural zone in particular. This study investigated how this training and extension of the technologies has empowered rural women to become entrepreneurs at various levels. A structured interview scheduled, were administered to 120 farmers in 2 agricultural zones of Abia (Ohafia and Umuahia). Data collected were analysed using descriptive and inferential statistics like linear regression model and t-test was used to test the hypothesis. The result revealed that majority of the respondents were married (88%) while 12% were single and were reasonably aware of the technologies. However, on the utilization of the technologies, out of the 5 processing technologies, only 3 had high level of utilization, processing of cocoyam into cake (=3.7) Bread (3.5 and Chin-chin (=3.2). Also a tangible impact was made in the livelihood of the respondents as there was a reasonable difference in income of the respondents after the training. The major challenges associated with the utilization were no extension agents to answer their questions (=3.90) lack of commitment = (Â =3.25 and marketing of product = (=3.17) among others. It is therefore recommended that re-training and provision of market facilities should be intensified to enhance the utilization of the processing technologies and their impact among the respondents.